Design and Analysis of Low-Cost and Efficient SEPIC Converter for Affordable Solar Water Pump in Ethiopia - Tanashu, Minyahil; Tadiwos, Tassew; Kassaw, Amare; Admasu, Seifu; Ezra, Noam; Long, Teng; Allen, Lara; Tennyson, Elizabeth M; Stranks, Sam; Yetayew, Tefera (Trans Tech Publications, 2024)
Abstract. Smallholder farms provide a significant share of the world's food supply. Smallholder farmers can cultivate crops more consistently throughout the year when using solar water pumps, which offer a dependable source of irrigation. However, the upfront capital cost and efficiency are major barriers to widespread adoption. This paper aimed to design a cost-effective and efficient DC-DC converter for small-scale irrigation farming in the Dangishta, Amhara region of Ethiopia, focusing on a direct solar water pump system using a SEPIC-based DC-DC converter. The system directly supplies power to a 100 W/24 V brushless DC pump, with a 120 W/24 V/5 A optimized SEPIC converter. A PLECS simulation was conducted to understand the converter's operation. The prototype design considered enhanced power handling capabilities using the paralleling method. The power switches are controlled by a digital circuit based on the RP2040 microcontroller, which generates PWM signals with a fixed duty cycle at 100 kHz. The average material cost of the converter was significantly minimized to approximately $15. Experimental tests showed an efficiency of 93.5% and an average temperature of 31°C, making it a promising solution for sustainable agriculture in resource-constrained environments.Keywords— Smallholder farms, Low-cost, SEPIC converter, Solar water pump, PLECS
Keywords: 40 Engineering; 4009 Electronics, Sensors and Digital Hardware